Damping performance of YSZ coating prepared by different EB-PVD parameters. (2nd January 2019) - Du, Guangyu; Li, Zhuolong; Tan, Zhen; Li, Guohao; Lin, Zeng; Ba, Dechun
ABSTRACT: A yttrium-stabilised zirconia (YSZ) coating was prepared on Ti–6Al–4 substrates by electron beam physical vapour deposition (EB-PVD). The effect of substrate temperature and beam intensity on the microstructure of the coating was researched. Damping characteristics of the coatings under different processing parameters were compared. The microstructure and crystal structure were determined with scanning electron microscope (SEM) and X-Ray Diffraction (XRD), respectively. The damping properties of the coating were measured by dynamic mechanical analyzer (DMA). The decrease in the substrate temperature leads to diminution of the grain size of coating, which increases the loss factor ( Q −1 ). The crystal defects and micro-cracks of the coating are also the main reasons for the improvement of the damping performance.